A Review of Anticancer Potential of Conferone, Diversin and Ferutinin; Which One is Stronger for Cancer Therapy? - Keshmirshekan, Fariborz; Mohamadi-Zarch, Seyed-Mahdi; Bagheri, Seyyed Majid (Anti-Cancer Agents in Medicinal Chemistry, 2025)
BackgroundOne of the growing diseases in today's human societies is cancer, which has become a major challenge, especially in industrialized and developing countries. Cancer treatments are diverse, but they usually use surgery, chemotherapy, and radiotherapy to improve patients. Existing drugs are usually expensive and, in some cases, are not effective due to drug resistance and side effects. Finding compounds of natural origin can be somewhat effective and useful in helping doctors to treat this disease. Ferula plants, which are traditionally used as spices or for medicinal purposes, can be a good source for finding anti-cancer compounds due to their various compounds, such as monoterpenes, sulfide compounds, and polyphenols. Several studies have shown that compounds found in Ferula plants have significant anticancer effects on various types of cancer cells.ObjectiveThis article was compiled with the aim of collecting evidence and articles related to the anti-cancer effects of three compounds obtained from these plants, namely Conferone, Diversin, and Ferutinin.MethodsThis review article was prepared by searching the terms Conferone, Diversin, Ferutinin and cancer and related information was collected through searching electronic databases such as ISI Web of Knowledge, PubMed and Google Scholar until the March of 2024.ConclusionThe results of this review showed that relatively comprehensive studies have been conducted in this field and these studies have shown that these compounds can be used in the design of future anticancer drugs. Among the examined compounds, conferone showed that it has the best effect on cancer cells.
Keywords: conferone